Artificial Photosynthesis - concluding remarks - Bozal-Ginesta,C; Durrant,JR (Faraday Discussions, 2019)
This paper follows on from the Concluding Remarks presentation of the 3rd Faraday Discussion Meeting on Artificial Photosynthesis, Cambridge, UK, 25-27th March 2019. It aims to discuss the context for the research discussed at this meeting, starting with an overview of the motivation for research on artificial photosynthesis. It then goes onto analysing the composition and trends in the field of artificial photosynthesis, and its scale relative to other related research areas, primarily using the results of searches of publication data bases. As such, we hope it provides helpful insights to researchersin the field.